Periodization of psychological preparation within the training process - Blumenstein, B.; Orbach, I. (International Journal of Sport and Exercise Psychology, 2020)
Psychological preparation (PP) is an essential fundamental factor of any sport training programme. This preparation is critical and influential in the athlete`s success. Periodization is a basic principle in sport training which enables the coach to plan and manage the training process. A typical training programme consists of three main phases: preparatory, competitive, and transition. The practice within these phases includes four different preparations: physical, technical, tactical, and psychological. Within the ideal training programme each of the four preparations should be coordinated with the other preparations in each training phase. In this paper, the integration of PP within the training phase is discussed and described by the periodization principle. The periodization of biofeedback training as applied in the Learning-Modification-Application approach framework and the transfer of learned psychological skills to the field while using the Simulation Training Programme has proven to be effective while working with elite athletes. Real-world evidence for the effectiveness of this idea was investigated in numerous research studies and in practical work with 38 medalists from 14 different sport disciplines in various top-level events.